The Relationship between Halal Logistics Practices and Organisational Competitiveness: A Study on Halal Food Industry in Kuala Lumpur, Malaysia - Thillai Raja Pertheban; Taha Mazen (International Journal of Supply Chain Management, 2022)
The largest and fastest-growing market in recent years is the Halal sector, which has received limited attention. The halal market is extremely competitive, and halal logistics are crucial to the growth of the halal food industry in Malaysia. The purpose of this study is to examine the relationship between Halal logistics practices and Organisational Competitiveness of Halal food industry in Kuala Lumpur, Malaysia. Quantitative analysis performed on a survey data of 108 respondents from Halal Industry in Kuala Lumpur. The novel findings affirm that halal logistics practices, such as Halal Equipment, Halal Safety and Halal Transport Information System positively affect Organisational Competitiveness in Halal Industry in Kuala Lumpur. Managers/logisticians should aware that halal value creation in halal logistics practices have a positive effect on halal organisations competitiveness. The results draw the novel contributions of the importance of halal logistics practices to sustain halal organisational competitiveness in Malaysia.